RAGAM BAHASA PENAWARAN PEDAGANG ASONGAN DI PANTAI PANGANDARAN - Fauziyyah, Desti Fatin (JURNAL PESONA, 2017)
This study was conducted to assess various languages trader deals in Pangandaran Beach in terms of perspektik sociolinguistics. The aim of research to find out the deals utterances used by hawkers at Pangandaran Beach, knowing offers a variety of language used by hawkers at Pangandaran Beach, and knowing use of vocabulary that deals used by hawkers at Pangandaran Beach. This study used a qualitative approach. The method used in this research is descriptive and analytical. The data used in this research is data in the form of a variety of language associated with language diversity offers Pangandaran beach hawkers. The results of the study deals buying and selling a variety of language, which is rarely done because of language preservation demands an understanding of the other person.Â